Synthesis, Antimicrobial, Anticancer Evaluation of 2-(aryl)-4- Thiazolidinone Derivatives and their QSAR Studies - Deep, Aakash; Kumar, Pradeep; Narasimhan, Balasubramanian; Ramasamy, Kalavathy; Mani, Vasudevan; Kumar Mishra, Rakesh; Bakar Abdul Majeed, Abu (Current Topics in Medicinal Chemistry, 2015)
A new class of 4-thiazolidinones clubbed with quinozolinone nucleus has been synthesized. The title compounds were screened for their in vitro antimicrobial and anticancer potentials. Results of antimicrobial and anticancer study revealed that compounds 7 (pMICam = 1.69 μM/ml) and 2 (IC50 = 12.83 μM) were found to be the most potent antimicrobial and anticancer agents respectively. QSAR studies indicated that antimicrobial activity of synthesized 4-thiazolidinone derivatives was governed by the electronic parameters, dipole moment (μ), energy of highest occupied molecular orbital (HOMO), lipophilic parameter, log P and topological parameter, valence third order molecular connectivity index (3χv).
Keywords: Antifungal